ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN KONSUMEN TERHADAP LISTRIK PADA RUMAH TANGGA DI DESA GUNTARANO KECAMATAN TANANTOVEA KABUPATEN DONGGALA - Bachtiar, Muhammad (Katalogis, 2013)
The purpose of this research to know and analysis for income factor with parsial and simultaneous, price and rate, amount the tools use the electric, the individual into family and the wide of building towards electric demand in consumer household in Guntarano village of Tanantovea district of Donggala Regency. The research population are 60 households that have electric network in PLN (state electric company). Remember the research population is limited relatively, that only 60 households that have electric network from PLN, so that the samples are all population in research or use a census technique where that all population member get opportunity as the sample. The collecting of primary and secondary data have been done by questionnaire and documentation. Thus, hypothesis test in research use multiple linear regression analysis method, the result of research indicate that income factor, price and rate, amount the tools use the electric, the individual into family and the wide of building with parsial and simultaneous which affect with significance towards the household electric demand in Guntarano village of Tanantovea district of Donggala Regency, and there are the factor that support and constrain of household electric demand in Guntarano village of Tanantovea district of Donggala Regency.